MEDIA PEMBELAJARAN WAYANG KERTAS UNTUK MENDUKUNG PROSES PENCERITAAN DALAM RANGKA MENGEMBANGKAN MORAL ANAK USIA SEKOLAH DASAR - Pramudya Cahyandaru; Bherrio Dwi Saputra; Ida Megawati; Eka Ridha Nofrida (STKIP Subang, 2022)
The challenge of education in the current era of disruption is to produce children who are able to think creatively, critically, innovatively, and with interdisciplinary and multidisciplinary sensitivity. Moral learning needs to be done as early as possible, according to the stages of children's moral development. Children's moral development is facilitated through learning activities that aim to provide moral knowledge to children. Children's knowledge can be developed through stories that are held through learning activities. The moral development of children through methods supported by wayang media is expected to facilitate early childhood learning. The wayang media presented not only features characters that match the character of each character but is also equipped with dialogue that allows reciprocity between children and wayang characters.